Gender Transformative Approaches Learning Workshop Report - Mudege, Netsayi; Kilanga, Lucyphine; Kakwasha, Keagan; Lukanga, Editrudith (WorldFish, 2024)
This report presents the proceedings and outcomes of the 2-day workshop to document lessons learned. A total of 47 participants attended the workshop, including women fish processors, fishermen, journalists, representatives of Beach Management Units (BMUs), government authorities in the district and region, civil society organizations, and research and development organisations.